INFORMATIZAÇÃO DA GESTÃO DA MANUTENÇÃO DE EQUIPAMENTOS UM CASO BASE: ANÁLISE E PROPOSTA DE MELHORIA - Arese, Marcelo Contente (2003)
According to ABRAMAN ( Associação Brasileira de Manutenção Brazilian Association of Maintenance), Computer Science in the Brazilian industry maintenance area has been increasing in the last years. Being aware that the use of Computer Science in maintenance is a broad process and that it requires very well planned changes, the Board of Directors of Fábrica Carioca de Catalisadores (a catalyzer plant in Rio de Janeiro state) has ordered this study, which will be the basis to implement the use of computer managed maintenance system MAXIMO (a software). This project presents an analysis and proposals to improve the process of maintenance management of equipments of the Fábrica Carioca de Catalisadores. It is prepared in 3 steps: the first is a bibliographical research on maintenance management. Then it is prepared the current situation mapping and an analysis compared to the theoretical referral. Finally, improvement proposals for the current management and a practical model for the use of the software MAXIMO are presented